Passively versus actively detected malaria: similar genetic diversity but different complexity of infection - Pava, Z; Handayuni, I; Trianty, L; Utami, RAS; Tirta, YK; Puspitasari, AM; Burdam, F; Kenangalem, E; Wirjanata, G; Kho, S; Trimarsanto, H; Anstey, N; et al. (American Society of Tropical Medicine and Hygiene, 2017)
The surveillance of malaria is generally undertaken on the assumption that samples passively collected at health facilities are comparable to or representative of the broader Plasmodium reservoir circulating in the community. Further characterization and comparability of the hidden asymptomatic parasite reservoir are needed to inform on the potential impact of sampling bias. This study explores the impact of sampling strategy on molecular surveillance by comparing the genetic make-up of Plasmodium falciparum and Plasmodium vivax isolates collected by passive versus active case detection. Sympatric isolates of P. falciparum and P. vivax were collected from a large community survey and ongoing clinical surveillance studies undertaken in the hypomesoendemic setting of Mimika District (Papua, Indonesia). Plasmodium falciparum isolates were genotyped at nine microsatellite loci and P. vivax at eight loci. Measures of diversity and differentiation were used to compare different patient and parasitological sample groups. The results demonstrated that passively detected cases (symptomatic) had comparable population diversity to those circulating in the community (asymptomatic) in both species. In addition, asymptomatic patent infections were as diverse as subpatent infections. However, a significant difference in multiplicity of infection (MOI) and percentage of polyclonal infections was observed between actively and passively detected P. vivax cases (mean MOI: 1.7 ± 0.7 versus 1.4 ± 1.4, respectively; P = 0.001). The study findings infer that, in hypomesoendemic settings, passive sampling is appropriate for molecular parasite surveillance strategies using the predominant clone in any given infection; however, the findings suggest caution when analyzing complexity of infection. Further evaluation is required in other endemic settings.